P42 Evaluating the impact of triple combination modulators on medication adherence in cystic fibrosis. Issue 5 (20th April 2022) - Sutton, Sharon; McNally, Paul; Howlett, Moninne; Hayden, John
Abstract : Aim: To measure the impact of introduction of triple combination modulator (TCM) therapy on adherence to other cystic fibrosis (CF) therapies. Method: This study is a multi-site non-interventional study of clinical outcomes in CF patients prescribed TCM across 8 clinical sites in Ireland and the UK over 2 years. The study will be conducted over two phases based on TCM approval: 1. 12+ arm (patients 12 years and older), 2. 6+ arm (patients 6-11 years). The effect of the potential drop-off in adherence to TCM is unknown and this knowledge gap will be examined using three methods; self-reported questionnaires (SRQ) [e.g. Treatment adherence questionnaire (TAQ) and Adherence barrier questionnaire (ABQ)]; pharmacy refill data (to calculate Medication Possession Ratio); and electronic devices such as Medication Electronic Monitoring System (MEMS®). Self-report tools and pharmacy refill data will be collated for all participants but due to high cost MEMS will be offered to a subset only (approx. 80 participants). Results: To date, 113 participants have been recruited to the 12+ arm. Recruitment and data collection is ongoing. Preliminary analysis of Medication Possession Ratio (n=5) demonstrated that baseline adherence to hypertonic saline, azithromycin, enzymes and Pulmozyme® was low to moderate, further decreasing after TCM introduction. No change for enzymes was found. Adherence to modulators was high, with further increases seen after TCM introduction. Self-report questionnaires (TAQ and PTP) were reviewed for a random 10% of current recruits (n=11). The mean Overall Adherence Index was 90.2%. At 6-month time point, 100% TCM adherence was reported. Airway clearance was the most frequently overlooked treatment with a 10.6% reduction in adherence from baseline to 6 months. Initial recruitment for MEMS® was high (95% recruitment target met) with 60% of participants remaining on the study. Average 'taking adherence' using MEMS® for was 78.2% and 82% for Kaftrio® (n=11) and Kalydeco® (n=10) respectively. Overall adherence to TCM using MEMS® was 78.9%. Conclusion: These early preliminary results suggest that adherence to TCM is overestimated in SRQs and pharmacy data in comparison to MEMS®. These trends are similar to those shown in previous studies [1-3]. As a result of the high dropout rate a feedback form has been developed to gain a better insight into the reasons why continued participation is low. Recruitment and data collection is ongoing. 6+ arm is due to commence recruiting in Q4 2021. References: Mehta Z, Kamal KM, Miller R, Covvey JR, Giannetti V. Adherence to cystic fibrosis transmembrane conductance regulator (CFTR) modulators: analysis of a national specialty pharmacy database. J Drug Assess 2021;10 :62-67. Stirratt MJ, Dunbar-Jacob J, Crane HM, Simoni JM, Czajkowski S, Hilliard ME, et al . Self-report measures of medication adherence behavior: recommendations on optimal use. Translational Behavioral Medicine 2015;5 :470-482. Siracusa CM, Ryan J, Burns L, Wang Y, Zhang N, Clancy JP, et al . Electronic monitoring reveals highly variable adherence patterns in patients prescribed ivacaftor. Journal of Cystic Fibrosis: Official Journal of the European Cystic Fibrosis Society 2015;14 :621-626.